1999
DOI: 10.1116/1.590511
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for liquid indium nanoparticles on Ge(001) at room temperature

Abstract: Indium films up to 6 ML thick on the Ge͑001͒ surface in ultrahigh vacuum have been both deposited at and investigated at room temperature. The investigation techniques used were scanning tunneling microscopy ͑STM͒, Auger electron spectroscopy ͑AES͒, x-ray photoelectron spectroscopy ͑XPS͒, and low energy electron diffraction. Correlated AES and STM observations strongly suggest In-Ge intermixing, while XPS rules out compound formation. For a film 5 ML thick, nanoparticles approximately 15 nm high and 60 nm acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…1,2 A recent study of P doped Ge͑100͒ suggested an alternative explanation; that P segregates to the surface during annealing and forms GeP 3 which then appears as nanoscale white dots on the surface. 4 Their STM images were similar to ours with many white protrusions and holes suggesting a similar origin, even though there was no evidence of the presence of P, or any other impurity, in our AES data and our wafer was undoped. Thus, it is unclear if the white dots observed in the recent study were indeed GeP 3 or trace contaminants or defects commonly observed on Ge͑100͒ surfaces.…”
Section: A Ion Bombardment and Annealingsupporting
confidence: 75%
See 1 more Smart Citation
“…1,2 A recent study of P doped Ge͑100͒ suggested an alternative explanation; that P segregates to the surface during annealing and forms GeP 3 which then appears as nanoscale white dots on the surface. 4 Their STM images were similar to ours with many white protrusions and holes suggesting a similar origin, even though there was no evidence of the presence of P, or any other impurity, in our AES data and our wafer was undoped. Thus, it is unclear if the white dots observed in the recent study were indeed GeP 3 or trace contaminants or defects commonly observed on Ge͑100͒ surfaces.…”
Section: A Ion Bombardment and Annealingsupporting
confidence: 75%
“…In other work, surface protrusions were attributed to surface segregation of dopants. 4 The protrusions, however, appeared very similar to those observed on undoped samples, thus raising questions about the assignment of the features to dopant segregation. The step pinning by the protrusions can also lead to problems.…”
Section: Introductionmentioning
confidence: 69%
“…XXXX, XXX, XXX−XXX at room temperature. 50 For this reason, we evaluated their capacity to facilitate ec-LLS crystal growth. We first prepared In nanoparticles on degenerately doped n-type Si(100) (n + -Si(100)) wafers via pulse electroplating.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…The thermodynamically stable shape of the islands is determined by the energies of the surface facets, facet edges, and interfaces [1][2]. To control the size and shape of the island, these energies can be modified, possibly by introducing additional species onto the growing surface [3][4][5].…”
Section: Introductionmentioning
confidence: 99%